ANALISIS HARGA SAHAM PERUSAHAAN SUB SEKTOR HOTEL, RESTORAN DAN PARIWISATA DI BURSA EFEK INDONESIA - Khiqna Anindiya Hanum, - (2019)
This research was conducted to determine the effect of firm size, profitability, and capital structure of stock prices. The population in this study were all hotel, restaurant and tourism companies at Indonesia Stock Exchange, which numbered 27 companies in the period 2013-2017. The sampling technique used was purposive sampling, so that the final sample obtained was 12 companies. The data collection method used in this study is non-behavioral observation. The data source in this study is secondary data obtained from Indonesia Stock Exchange website and Dunia Investasi website. The data analysis technique used is descriptive statistics and panel data regression analysis with the help of Microsoft Excel 2010 applications and E-Views version 9.0. Based on the results of the analysis show that firm size and profitability has a positive significant effect on stock prices and capital structure does not effect on stock prices.